2022
DOI: 10.1186/s43088-022-00242-y
|View full text |Cite
|
Sign up to set email alerts
|

Sepia officinalis ink mitigates gastric ulcer via modulation of antioxidant/anti-inflammatory pathways

Abstract: Background Sepia officinalis ink is a bioactive secondary metabolite rich in melanin granules, which has a wide range of nutritional and therapeutic values and also has been used to prevent various gastrointestinal disorders. Gastric ulcer, the most common gastrointestinal disease, is characterized by severe gastric mucosa damage, and its prevention is currently one of the main goals of clinical and experimental studies. Thus, the present study was focused on evaluating the potential gastroprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Ethanol intake predominantly damages the glandular portion of the stomach since it penetrates rapidly in to the gastric mucosa and leads to gastric lesion such as extensive submucosal edema, hemorrhage, desquamation of epithelial cells and infiltration of inflammatory cells (Mousa et al, 2019;Ciciliato et al, 2022;Sadek, 2022). The repeated oral dose study for ethanol-induced ulcer model showed a significant reduction in ulcer index (p< 0.05) in 6, 10 and 14 days treatment with O. crinita at dose 200mg/kg.…”
Section: Discussionmentioning
confidence: 97%
“…Ethanol intake predominantly damages the glandular portion of the stomach since it penetrates rapidly in to the gastric mucosa and leads to gastric lesion such as extensive submucosal edema, hemorrhage, desquamation of epithelial cells and infiltration of inflammatory cells (Mousa et al, 2019;Ciciliato et al, 2022;Sadek, 2022). The repeated oral dose study for ethanol-induced ulcer model showed a significant reduction in ulcer index (p< 0.05) in 6, 10 and 14 days treatment with O. crinita at dose 200mg/kg.…”
Section: Discussionmentioning
confidence: 97%
“…The homogenate was centrifuged at 10,000 rpm for 20 min for removing the cell debris, unbroken cells, nuclei, erythrocytes and mitochondria. The supernatant (cytoplasmic extract) was used to measure PRKACA, BDNF, IL-6, Dopamine, Cortisol, SOD and MDA according to the manual instructions [ 27 ].…”
Section: Behavioral Testsmentioning
confidence: 99%